Hierarchical Micro/Nanofibrous Bioscaffolds for Structural Tissue Regeneration. Issue 13 (13th April 2017) - Xu, Yun; Cui, Wenguo; Zhang, Yanxia; Zhou, Pinghui; Gu, Yong; Shen, Xiaofeng; Li, Bin; Chen, Liang
Abstract : Various biomimetic scaffolds with hierarchical micro/nanostructures are designed to closely mimic native extracellular matrix network and to guide cell behavior to promote structural tissue generation. However, it remains a challenge to fabricate hierarchical micro/nanoscaled fibrous scaffolds with different functional components that endow the scaffolds with both biochemical and physical features to exert different biological roles during the process of tissue healing. In this study, a biomimetic designed micro/nanoscaled scaffold with integrated hierarchical dual fibrillar components is fabricated in order to repair dura mater and prevent the formation of epidural scars via collagen molecule self‐assembly, electrospinning, and biological interface crosslinking strategies. The fabricated biomimetic scaffolds display micro/nanofibers staggered hierarchical architecture with good mechanical properties and biocompatibility, and it has a more profound effect on attachment, proliferation, and differentiation of fibroblasts. Using a rabbit duraplasty model in vivo, the authors find that dural defects repaired with hierarchical micro/nanoscaled scaffold form a continuous neodura tissue similar to native dura mater; furthermore, the number of scar tissues decreases significantly in the laminectomy sites compared with conventional electrospun microfibrous scaffold. Taken together, these data suggest that the hierarchical micro/nanoscaled fibrous scaffolds with dual fibrillar components may act as a "true" dural substitutes for dual repair. Abstract : A biomimetic micro/nanoscaffold with integrated hierarchical dual fibrillar components is fabricated via collagen self‐assembly, electrospinning, and biological interface crosslinking strategies. Hierarchical micro/nanoscaled fibrous scaffolds can not only induce the formation of new tissue of dura mater, but also mitigate the formation of spinal epidural scar fibrosis through scaffold medicated component modulation for epidural tissue structural remodeling.